HPLC Quantification of All Five Ginkgolic Acid Derivatives in Ginkgo biloba Extracts using 13 : 0 Ginkgolic Acid as a Single Marker Compound - Wang, Ruwei; Kobayashi, Yuta; Lin, Yu; Rauwald, Hans Wilhelm; Yao, Jianbiao; Fang, Ling; Qiao, Hongxiang; Kuchta, Kenny (Planta Medica, 2015)
An HPLC quantification method for ginkgolic acid derivatives in Ginkgo biloba leaf extracts was developed. Using 13 : 0 ginkgolic acid as a marker compound, the relative correlation factors of the four other ginkgolic acid derivatives – namely, 15 : 0 ginkgolic acid, 15 : 1 ginkgolic acid, 17 : 1 ginkgolic acid, and 17 : 2 ginkgolic acid – to 13 : 0 ginkgolic acid were determined by HPLC and subsequently used for calculating their contents in ten hydro-ethanolic refined extract samples. In other words, the content of 13 : 0 ginkgolic acid in the extracts was determined using the isolated compound as an external standard. Subsequently the now known concentration of this compound functioned as an internal standard for the quantification of the other four ginkgolic acid derivatives via the described correlation factors. This HPLC method was validated by two independent control measurements, one with an external standard for every individual compound and one based on the present method with the single marker compound alone. The results did not differ significantly in any of the 10 tested extract samples. The protocol presented here thus not only uses the same reference substance for G. biloba extracts as the current Chinese Pharmacopoeia method but also incorporates the advantages of the current European Pharmacopoeia approach. It is simple, reproducible, and can be used to determine the total contents of ginkgolic acid derivatives in G. biloba leaf extracts.
Keywords: Ginkgo biloba; Ginkgoaceae; ginkgolic acid derivatives; relative correlation factor; HPLC; quantitative analysis